1991
DOI: 10.1159/000108856
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate Endothelial Damage on the in vivo Reactivity of Pial Arteries to Norepinephrine and Serotonin

Abstract: Most of the information on the role of the endothelium for the vascular reactivity comes from in vitro experiments on noncerebral vessels. Few studies address the contribution of the endothelium to the cerebrovascular reactions in vivo. In the present study, arterial cerebral air embolism was employed to induce endothelial damage in anesthetized cats. The endothelial injury was verified by scanning electron microscopy: air embolism induced obvious damage to the endothelial layer, consisting of flattening, supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In the latter case, the response to 5-HT varied in relation to the vessel diameter, the smaller arterioles /arteries dilating and the larger ones constricting. However, another study on cat pial arteries in situ did not confirm the existence of such a relationship or such dilatory responses (9). A recent study on human intracortical arterioles showed a biphasic response to the 5-HT1B/D agonist sumatriptan, the small relaxation at low concentration being abolished by nitric oxide synthase inhibition (10).…”
mentioning
confidence: 95%
“…In the latter case, the response to 5-HT varied in relation to the vessel diameter, the smaller arterioles /arteries dilating and the larger ones constricting. However, another study on cat pial arteries in situ did not confirm the existence of such a relationship or such dilatory responses (9). A recent study on human intracortical arterioles showed a biphasic response to the 5-HT1B/D agonist sumatriptan, the small relaxation at low concentration being abolished by nitric oxide synthase inhibition (10).…”
mentioning
confidence: 95%
“…A recent study 9 reported that norepinephrine dilates pial arterioles at low concentrations but produces vasoconstriction at high concentrations in cats. The authors observed that constrictor responses to norepinephrine were preserved after injury to arteriolar endothelium produced by air embolism.…”
Section: Figure3 Effect Of Vasopressin (Avp 10~9 and 10' 8 M) On Cementioning
confidence: 99%